Identification of human intestinal parasites affecting an asymptomatic peri-urban Argentinian population using multi-parallel quantitative real-time polymerase chain reaction - Cimino, Rubén O.; Jeun, Rebecca; Juarez, Marisa; Cajal, Pamela S.; Vargas, Paola; Echazú, Adriana; Bryan, Patricia E.; Nasser, Julio; Krolewiecki, Alejandro; Mejia, Rojelio (Parasites & vectors, 2015)
Background In resource-limited countries, stool microscopy is the diagnostic test of choice for intestinal parasites (soil-transmitted helminths and/or intestinal protozoa). However, sensitivity and specificity is low. Improved diagnosis of intestinal parasites is especially important for accurate measurements of prevalence and intensity of infections in endemic areas. Methods The study was carried out in Orán, Argentina. A total of 99 stool samples from a local surveillance campaign were analyzed by concentration microscopy and McMaster egg counting technique compared to the analysis by multi-parallel quantitative real-time polymerase chain reaction (qPCR). This study compared the performance of qPCR assay and stool microscopy for 8 common intestinal parasites that infect humans including the helminths Ascaris lumbricoides, Ancylostoma duodenale, Necator americanus, Strongyloides stercoralis, Trichuris trichiura, and the protozoa Giardia lamblia, Cryptosporidium parvum/hominis, and Entamoeba histolytica, and investigated the prevalence of polyparasitism in an endemic area. Results qPCR showed higher detection rates for all parasites as compared to stool microscopy except T. trichiura . Species-specific primers and probes were able to distinguish between A. duodenale (19.1 %) and N. americanus (36.4 %) infections. There were 48.6 % of subjects co-infected with both hookworms, and a significant increase in hookworm DNA for A. duodenale versus N. americanus (119.6 fg/μL: 0.63 fg/μL, P < 0.001) respectively. qPCR outperformed microscopy by the largest margin in G. lamblia infections (63.6 % versus 8.1 %, P < 0.05). Polyparasitism was detected more often by qPCR compared to microscopy (64.7 % versus 24.2 %, P < 0.05). Conclusions Multi-parallel qPCR is a quantitative molecular diagnostic method for common intestinal parasites in an endemic area that has improved diagnostic accuracy compared to stool microscopy. This first time use of multi-parallel qPCR in Argentina has demonstrated the high prevalence of intestinal parasites in a peri-urban area. These results will contribute to more accurate epidemiological survey, refined treatment strategies on a public scale, and better health outcomes in endemic settings.